2015
DOI: 10.1038/ejcn.2015.121
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 24-h creatinine excretion in adults and its use as a simple tool for the estimation of daily urinary analyte excretion from analyte/creatinine ratios in populations

Abstract: The present mean values of 24-h creatinine excretion are suggested as a useful tool to derive realistic hydration-status-independent average 24-h excretion rates from urinary analyte/creatinine ratios. We propose to apply these creatinine reference means routinely in biomarker-based studies aiming at characterizing the nutrient or metabolite status of adult populations by simply measuring metabolite/creatinine ratios in spot urines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Box-Whisker-Plot of estimated daily creatinine excretion in mmol/d using various methods [31][32][33]36]. Presented are median and interquartile range (box) and the 5th and 95th percentile (whiskers) Table 5 Correlation of creatinine estimates obtained with various equations Kawasaki [33] Tanaka [32] Toft [31] Johner [36] Kawasaki [ [50] concluded that the estimates with Kawasaki's equation were the least biased. Brown's equation, in contrast, seems to underestimate daily sodium excretion by a differing degree [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Box-Whisker-Plot of estimated daily creatinine excretion in mmol/d using various methods [31][32][33]36]. Presented are median and interquartile range (box) and the 5th and 95th percentile (whiskers) Table 5 Correlation of creatinine estimates obtained with various equations Kawasaki [33] Tanaka [32] Toft [31] Johner [36] Kawasaki [ [50] concluded that the estimates with Kawasaki's equation were the least biased. Brown's equation, in contrast, seems to underestimate daily sodium excretion by a differing degree [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Five equations to estimate sodium excretion within 24 h from spot urine concentrations of sodium and creatinine were identified from literature [28,[31][32][33][34][35][36] and applied to the dataset. Table 1 provides key information on the study populations that have been used to derive the equations.…”
Section: Urine Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, taking into account a creatinine correction factor, the dietary intake of potassium can be estimated [18,19]. In addition, the urinary potassium excretion has to be corrected by the absorption and the excretion rate of potassium.…”
Section: Derivation Of the Reference Values For Potassium Intakementioning
confidence: 99%